Implementation of Supply Chain Management and Strategic Planning in Agri-food Industries - Alim B. Nagoev; Aleksandr V. Smetanko; Violetta V. Rokotyanskaya; Ilya N. Lenkov; Vladimir A. Gorbachev (International Journal of Supply Chain Management, 2020)
Abstract- The article discusses the implementation of strategic planning in the agricultural sector. The aim of the study is to justify the priority development of the industry as the basis for a new level of agri-industrial complex evolution. It has been suggested that the existing in some sectors of the agro-industrial complex management mechanism is not efficient enough, since it doesn’t take into account modern challenges and the requirements of a dynamically changing external environ-ment.